Attitudinal Perspectives and Academic Implications of Peer-led Discussions in Grammar Learning - Agustina, Sheila; Megawati, Fika; Fediyanto, Niko; Fatima Virgiyanti, Diska (Universitas PGRI Adi Buana Surabaya, 2025)
This study investigates the relationship between students' attitudes toward the use of peer-led discussions in grammar class and their academic performance. Peer-led discussions, recognized for promoting active participation and collaborative learning, have been increasingly integrated into language education. However, their effectiveness in enhancing grammar proficiency remains unclear. This research involves 35 students from an English Education Program in a grammar class, with attitudes assessed using a 4-point Likert scale. The findings indicate a generally neutral to slightly negative attitude, with an average score of 2.96. Correlation analysis reveals a very weak positive relationship (r = 0.047) between students' attitudes and their academic performance, which is statistically insignificant (p = 0.788). These results suggest that while the method may foster engagement, it does not significantly improve grammar learning outcomes. The study concludes that the current implementation of peer-led discussions may not effectively meet students' learning needs in grammar instruction. Recommendations for future research include exploring alternative formats that better align with grammar learning objectives and investigating factors that influence students' attitudes more comprehensively.